Konflik Kognitif Internal Siswa dalam Menyelesaikan Masalah Matematika Ditinjau dari Proses Asimilasi Akomodasi - Ratnah Lestary; Subanji Subanji; Rustanto Rahardi (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2018)
This study aims to describe the internal cognitive conflicts that occur to students when they were solving mathematics problems. There were two participants in this research. They were 7th grade students from SMPN 1 Malang. The first participant was a student who has experienced internal cognitive conflicts and has capability to resolve it as well as the mathematics problems. Meanwhile, the second participant was a student who has experienced internal cognitive conflict but cannot resolve that conflict and also the mathematics problems. This research was used descriptive qualitative. The data of this study was gathered from students’ test on cognitive conflict and interview which was adapted from Newman's interview procedure. It was found that, the students who are able to find a relationship between the ratio of the number of workers and the number of chairs produced in a day, have capability to resolve their cognitive conflicts so that it brings them to the right problem solving. Meanwhile, the students that fail to build a relationship between the comparison concepts with mathematics problems and fail to find the relation between the numbers of people with the number of chairs in one day can not resolve the cognitive conflict so that they solve the problems in the wrong ways.